Measuring and Testing the Scalability of Cloud-based Software Services - Al-Said Ahmad, A; Andras, PE (Institute of Electrical and Electronics Engineers (IEEE), 2019)
Performance and scalability testing and measurements of cloud-based software services are critically important in the context of rapid growth of cloud computing and supporting the delivery of these services. Cloud-based software services performance aspects are interrelated, both elasticity and efficiency are depending on the delivery of a sufficient level of scalability performance. In this work, we focused on testing and measuring the scalability of cloud-based software services in technical terms. This paper uses technical scalability metrics that address both volume and quality scaling, that inspired by earlier technical metrics of elasticity. We show how our technical scalability metrics can be integrated into an earlier utility oriented metric of scalability. We demonstrate the application of the metrics using a practical example and discuss the importance of them.
This is the accepted author manuscript (AAM). The final published version (version of record) is available online via IEEE at https://doi.org/10.1109/ISIICT.2018.8613297 - please refer to any applicable terms of use of the publisher.
Keywords: QA75 Electronic computers. Computer science; Measurement; Performance; Testing; Scalability; Software-as-a-Service (SaaS); Metrics